Peptide‐Based Coacervate‐Core Vesicles with Semipermeable Membranes. Issue 34 (22nd July 2022) - Abbas, Manzar; Law, Jack O.; Grellscheid, Sushma N.; Huck, Wilhelm T. S.; Spruijt, Evan
Abstract: Coacervates droplets have long been considered as potential protocells to mimic living cells. However, these droplets lack a membrane and are prone to coalescence, limiting their ability to survive, interact, and organize into higher‐order assemblies. This work shows that tyrosine‐rich peptide conjugates can undergo liquid–liquid phase separation in a well‐defined pH window and transform into stable membrane‐enclosed protocells by enzymatic oxidation and cross‐linking at the liquid–liquid interface. The oxidation of the tyrosine‐rich peptides into dityrosine creates a semipermeable, flexible membrane around the coacervates with tunable thickness, which displays strong intrinsic fluorescence, and stabilizes the coacervate protocells against coalescence. The membranes have an effective molecular weight cut‐off of 2.5 kDa, as determined from the partitioning of small dyes and labeled peptides, RNA, and polymers into the membrane‐enclosed coacervate protocells. Flicker spectroscopy reveals a membrane bending rigidity of only 0.1 k B T, which is substantially lower than phospholipid bilayers despite a larger membrane thickness. Finally, it is shown that enzymes can be stably encapsulated inside the protocells and be supplied with substrates from outside, which opens the way for these membrane‐bound compartments to be used as molecularly crowded artificial cells capable of communication or as a vehicle for drug delivery. Abstract : Coacervate droplets are promising protocell candidates. However, these droplets lack a membrane and are prone to coalescence, limiting their survival and ability to interact. This work shows that short tyrosine‐rich peptide conjugates can undergo liquid–liquid phase separation and subsequently transform into stable membrane‐enclosed protocells by enzymatic oxidation. The coacervate‐core vesicles are semipermeable and can host enzymatic reactions.